Socioeconomic associations of improved maternal, neonatal, and perinatal survival in Qatar - Sajjad Rahman; Khalil Salameh; Abdulbari Bener; et al (Dove Medical Press, 2010)
Sajjad Rahman1,2, Khalil Salameh1, Abdulbari Bener1,3, Walid El Ansari41Women’s Hospital, Hamad Medical Corporation, Doha, Qatar; 2Department of Clinical Pediatrics, Weill Cornell Medical College, Doha, Qatar; 3Department of Evidence for Population Health Unit, School of Epidemiology and Health Sciences, University of Manchester, Manchester UK; 4Faculty of Applied Sciences, University of Gloucestershire, Gloucester, UKAbstract: This retrospective study analyzed the temporal association between socioeconomic development indices and improved maternal, neonatal, and perinatal survival in the State of Qatar over a period of 35 years (1974–2008). We explored the association between reduction in poverty, improvement in maternal education, and perinatal health care on the one hand, and increased maternal, neonatal, and perinatal survival on the other hand. Yearly mortality data was ascertained from the perinatal and neonatal mortality registers of the Women’s Hospital and the national database in the Department of Preventive Medicine at Hamad Medical Corporation in Doha. A total of 323,014 births were recorded during the study period. During these 35 years, there was a remarkable decline (P < 0.001) in Qatar’s neonatal mortality rate from 26.27/1000 in 1974 to 4.4/1000 in 2008 and in the perinatal mortality rate from 44.4/1000 in 1974 to 10.58/1000 in 2008. Qatar’s maternal mortality rate remained zero during 1993, 1995, and then in 1998–2000. The maternal mortality rate was 11.6/100,000 in 2008. For the rest of the years it has been approximately 10/100,000. Across the study period, the reduction in poverty, increase in maternal education, and improved perinatal health care were temporally associated with a significant improvement in maternal, neonatal, and perinatal survival. The total annual births increased five-fold during the study period, with no negative impact on survival rates. Neonatal mortality rates in Qatar have reached a plateau since 2005. We also conducted a substudy to assess the association between improvements in survival rates in relation to health care investment. For this purpose, we divided the study period into two eras, ie, era A (1974–1993) during which major health care investment was in community-based, low-cost interventions, and era B (1994–2008) during which the major health care investment was in high-technology institutional interventions. Although from 1974–1993 (era A) the per capita health expenditure increased by only 19% as compared with a 137% increase in 1994–2008 (era B). The decline in neonatal and perinatal mortality rates was three times steeper during era A than in era B. The decline in neonatal and perinatal mortality rates was also significant (P < 0.001) when analyzed separately for era A and era B. We concluded that across the 35-year period covered by our study, the reduction in poverty, increased maternal education, and improved perinatal health care were temporally associated with improved maternal, neonatal, and perinatal survival in the State of Qatar. From the subanalysis of era A and era B, we concluded that low-cost, community-based interventions, on the background of socioeconomic development, have a stronger impact on maternal, neonatal, and perinatal survival as compared with high-cost institutional interventions.Keywords: maternal, neonatal, perinatal, mortality rate, Qatar, health care costs